International Society for the History of the Neurosciences 24th Meeting in Vilnius, 2019 - Lazar, J. Wayne Wayne; Eling, Paul; Finger, Stanley; Jatužis, Dalius (Vilnius University Proceedings, 2019)
Mission of the International Society for the History of the Neurosciences (ISHN) 24th Meeting in Vilnius, 2019 is to improve communication between individuals and groups interested in the history of neuroscience, promote research in the history of neuroscience in Lithuania and worldwide, promote education and stimulate interest for the history of neuroscience.